Some Convergence and Stability Results for Two New Kirk Type Hybrid Fixed Point Iterative Algorithms - Faik Gürsoy; Vatan Karakaya (Journal of Function Spaces)
We introduce Kirk-multistep-SP and Kirk-S iterative algorithms and we prove some convergence and stability results for these iterative algorithms. Since these iterative algorithms are more general than some other iterative algorithms in the existing literature, our results generalize and unify some other results in the literature.